Proteolytic and Immunologic Comparison of Human and Bovine von Willebrand Factor - Bakhshi, Meenakshi R; Kirby, Edward P (Thrombosis and Haemostasis, 1990)
The structures of bovine and human vWF were compared by proteolysis with Staphylococcus aureus V8 protease and rattlesnake venom Protease I. Fragments were analyzed for chain composition, heparin binding, collagen binding, platelet agglutinating activity and recognition by a panel of monoclonal antibodies which reacted with both bovine and human vWF. Similar large fragments from the C-terminal domain of vWF were seen in each case. The N-terminal domain resulting from cleavage of bovine vWF was much smaller than that seen upon digestion of human vWF with V8 protease. Protease I destroyed the heparin binding domain in human vWF. Bovine vWF was much less sensitive to proteolysis than was human vWF.